Fabrication, microstructure, and properties of fired clay bricks using construction and demolition waste sludge as the main additive. (10th June 2020) - dos Reis, Glaydson Simões; Cazacliu, Bogdan Grigore; Cothenet, Alexis; Poullain, Philippe; Wilhelm, Michaela; Sampaio, Carlos Hoffmann; Lima, Eder Claudio; Ambros, Weslei; Torrenti, Jean-Michel
Abstract: Green routes to prepare or manufacture sustainable building materials have been attracting much attention over the years targeting sustainability issues. In this investigation, for the first time, sludge from the inert mineral part of the construction and demolition waste (RA-S) is used as a primary raw material in the fabrication of fired bricks for building purposes. Fired bricks fabricated with different dosages of RA-S and earth material (i.e., 0%, 30%, 50%, 70%, and 100% by weight) were prepared and evaluated in terms of their physical-chemical properties. The RA-S was characterized, and the results showed that it could be classified as a clayey material and richly graded silty sand according to the French Standards. XRD analysis revealed that the addition of the RA sludge into raw earth material provoked changes slightly in the fired bricks. The compressive strength (CS) results indicated that the CS of the fired bricks increased with the addition of the RA-S from 30% to 70%. The highest CS was attained at the firing temperature of 800 °C. The density of the fired brick slightly reduced with the RA-S addition. The thermal conductivity results suggest that RA-S has better insulation properties compared to earth material. The RA-S sludge can be used in combination with earth material to fabricate fired bricks, which can meet the requirements of many Standards all over the World. In the light of these results, it is possible to say that the RA-S generated from recycling inert mineral part of construction and demolition waste plant is an excellent raw material to prepare efficient fired bricks that can be successfully employed in the real construction sector. Also, the highlighted results suggest that brickwork factories have the opportunity to improve production quality while significantly reducing manufacturing time, energy consumption, resource depletion, and environmental impact. Graphical abstract: Image 1 Highlights: Construction and demolition waste sludge (RA-S) was used as efficient raw material for fired bricks manufacturing. The highest compressive strength was found for the brick prepared with 70% of RA-S and 30% of earth material fired at 800 °C. RA-S can be used to manufacture fired bricks, which can meet the requirements of many Standards all over the World. The thermal conductivity results suggest that RA-S has better insulation properties compared with raw earth material.